2011
DOI: 10.2319/050210-238.1
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of osteoprotegerin promotes preosteoblast differentiation to mature osteoblasts

Abstract: Objective: The hypothesis of the present study is that overexpression of osteoprotegerin (OPG) promotes preosteoblast maturation. Materials and Methods: The preosteoblast cell line MC3T3-E1 was transfected with OPG overexpression. OPG expression was confirmed by enzyme-linked immunosorbent assay (ELISA) and Western blot. Changes in the transcription factors in OPG-expressing cells were assessed by real-time polymerase quantitative polymerase chain reaction (RT-qPCR). Alkaline phosphate (ALP) expression was mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 27 publications
(42 reference statements)
1
23
2
Order By: Relevance
“…However, there were greater numbers of osteoblasts in the LO group in the present study than in the study by Demirer et al (20). Previous studies (22,23) have shown that over-expression of OPG stimulates the differentiation of pre-osteoblasts into mature osteoblasts. The increased number of osteoblasts observed in the present study might have been related to increased expression of OPG in the LO group.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…However, there were greater numbers of osteoblasts in the LO group in the present study than in the study by Demirer et al (20). Previous studies (22,23) have shown that over-expression of OPG stimulates the differentiation of pre-osteoblasts into mature osteoblasts. The increased number of osteoblasts observed in the present study might have been related to increased expression of OPG in the LO group.…”
Section: Discussioncontrasting
confidence: 66%
“…. Previous studies have shown that over‐expression of OPG stimulates the differentiation of pre‐osteoblasts into mature osteoblasts. The increased number of osteoblasts observed in the present study might have been related to increased expression of OPG in the LO group.…”
Section: Discussionmentioning
confidence: 98%
“…OPG (40 ng/mL) primed human mesenchymal stem cells demonstrated increased osteocalcin expression upon osteogenic induction (31). In addition, OPG overexpression in murine preosteoblasts resulted in increased ALP activity (32). In contrast, it has been shown that OPG (0.1-10 ng/mL) inhibited osteogenic differentiation in rat vascular smooth muscle cells, as determined by decreased ALP activity and mineralization (21).…”
Section: Discussionmentioning
confidence: 99%
“…A signal from AS plaque induces expression of potent osteogenic differentiation factor BMP-2a, with bone matrix and calcium hydroxyapatite crystals deposition in the arterial wall cells [41, 42]. Osteoprotegerin (OPG) [43, 44] inactivates the osteoclasts by blocking RANK activation. In dialysis patients, serum OPG levels are associated and predict progressive vascular calcification especially when CRP level is increased.…”
Section: Traditional Concepts In Esrd Patients With Vascular Calcimentioning
confidence: 99%